[Laiškai] / Borchova (Borchowa) Marija - Adomui Zavadskiui. - (:unkn) unknown (My University, 1856)
2 laiškai dėl muzikos, medicinos veikalų bei Lenkijos istorijos atsiuntimo.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Zawadzki, Adam, 1814-1875; Lenkija; Borchova (Borchowa), Marija